WGS Analysis of Clonal and Plasmidic Epidemiology of Colistin-Resistance Mediated by mcr Genes in the Poultry Sector in Lebanon - Al-Mir, Hiba; Osman, Marwan; Drapeau, Antoine; Hamze, Monzer; Madec, Jean-Yves; Haenni, Marisa (Frontiers in Microbiology, 2021)
Poultry and poultry meat are important contributors to the global antimicrobial burden. Unregulated and illegal use of extended-spectrum cephalosporins (ESC) in this sector has long been identified as a major cause of massive spread of ESC-resistant Escherichia coli, and colistin usage is considered a main driver of plasmid-mediated mcr genes dissemination. In Lebanon, the first mcr-1-positive E. coli found in poultry dates back to 2015, followed by a few reports of mcr-1-positive E. coli in poultry, swine, humans, and the environment. On the contrary, a comprehensive picture of the population structure of mcr-1-positive E. coli and mcr-1-bearing plasmids carrying the mcr-1 gene using whole-genome analysis is largely lacking. This study reports the prevalence of mcr-1-positive E. coli in poultry originating from 32 farms across three Lebanese governorates and slaughtered in the same place. We report 27/32 (84.4%) mcr-1 positive farms, leading to a total of 84 non-duplicate E. coli collected, of which 62 presented the mcr-1 gene. Numerous associated resistances were identified, including to ESC through the presence of blaCTX–M or blaCMY genes. The mcr-1 gene was mostly carried by IncX4 (n = 36) and IncI2 (n = 24) plasmids, which are both known for their efficient transfer capacities. A high genetic diversity was detected, arguing for the lack of contamination during the slaughter process. ST744 and ST1011 were the most widely identified clones, which have been both regularly associated to mcr-1-carrying E. coli and to the poultry sector. The wide dissemination of colistin-resistance, coupled to resistances to ESC and numerous other molecules, should urge authorities to implement efficient guidelines for the use of antibiotics in the poultry sector in Lebanon.